Cybercrime in ASEAN: Anti-Child Pornography Legislation - Smith, Robert Brian (Universitas Negeri Semarang, 2020)
Child pornography is one of the most pernicious crimes amongst the various forms of cybercrime. Offensive materials can be quickly disseminated over the internet with no respect for international borders. ASEAN leaders undertook at their 31st ASEAN Summit to prevent and tackle cybercrime including harmonising their laws. This paper is based on an analysis of the cybercrime legislation of all ten ASEAN countries to determine how the offence of child pornography is covered in their legislation. As the offence has extra-territorial consequences the analysis includes a discussion of the extraterritorial reach of the legislation. It was found that most of the jurisdictions have specific statutes or specific articles in their Criminal Codes concerning the crime of child pornography. They do not necessarily refer to cybercrime or computer-related crime. Mutual cooperation is essential in combating cybercrime as is legislation that clearly defines the offence and is agreed across all jurisdictions. The paper analyses the current status of harmonization of laws in ASEAN and discusses a possible way forward in the harmonization of anti-child pornography legislation across ASEAN.